The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.drugpo.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and HIV infection awareness among HIV-infected female sex workers in Lilongwe, Malawi

Abstract: Background HIV diagnosis, the first step in HIV care and treatment engagement, may be inhibited by substance use among female sex workers (FSW). We assessed the relationship between alcohol and marijuana use and lack of HIV infection awareness among HIV-infected FSW in Lilongwe, Malawi. Methods From July to September, 2014, 200 FSW aged ≥18 years were enrolled using venue-based sampling to examine substance use, HIV testing history, and serostatus ascertained by HIV rapid test. We used Poisson regression wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 71 publications
0
19
1
Order By: Relevance
“…Contrary to the Botswana study, these results found married persons to be more likely than single persons to be aware of their status and found no statistically significant association across education or mobility. The third study was conducted exclusively among female sex workers in Malawi, and investigated associations between substance use and Awareness of HIV‐Positive Status , finding those with alcohol dependency had 2.4‐fold greater prevalence of being unaware of their HIV‐positive status compared to non‐harmful use (95% CI 1.0 to 5.6), but found no associations for other levels of alcohol consumption or marijuana use [28].…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the Botswana study, these results found married persons to be more likely than single persons to be aware of their status and found no statistically significant association across education or mobility. The third study was conducted exclusively among female sex workers in Malawi, and investigated associations between substance use and Awareness of HIV‐Positive Status , finding those with alcohol dependency had 2.4‐fold greater prevalence of being unaware of their HIV‐positive status compared to non‐harmful use (95% CI 1.0 to 5.6), but found no associations for other levels of alcohol consumption or marijuana use [28].…”
Section: Resultsmentioning
confidence: 99%
“…These new diagnoses were made even though most participants reported having previously tested for HIV. These data align with recent evidence from Malawi where relatively few MSM and FSW living with HIV were previously aware of their HIV status . We estimate that over 2000 KPLHIV who do not currently know their status could be newly diagnosed if venue‐based HTS were expanded to all venues in the studied locales.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are few interventions focused on reducing substance use while improving ART uptake (Deering et al, 2009; Donastorg, Barrington, Perez, & Kerrigan, 2014), and none with FSW in sub-Saharan Africa. Substance use can impair cognitive functions, which in turn may adversely affect health seeking behaviour such as receiving and initiating HIV care and treatment (Chitwood, McBride, French, & Comerford, 1999; Tucker, Burnam, Sherbourne, Kung, & Gifford, 2003; Sohler et al, 2007; Simmonds & Coomber, 2009; Lancaster et al, 2016). Integrating substance use treatment with HIV care and treatment programmes, as resources allow, may reach FSW and improve HIV care and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%